Ex Vivo and In Vitro Analysis Identify a Detrimental Impact of Neutrophil Extracellular Traps on Eye Structures in Equine Recurrent Uveitis - Fingerhut, Leonie; Yücel, Leyla; Strutzberg-Minder, Katrin; von Köckritz-Blickwede, Maren; Ohnesorge, Bernhard; de Buhr, Nicole (Frontiers in Immunology, 2022)
Equine recurrent uveitis (ERU) is a common ocular disease of horses and described as a model for human autoimmune uveitis. This immune-mediated, inflammatory condition progressively destroys the eye, ultimately leading to blindness. Genetic and autoimmune factors are, next to infections with Leptospira, discussed as key factors in the pathogenesis. Furthermore, a release of neutrophil extracellular traps (NETs) by activated neutrophils is involved. NETs are composed of decondensed chromatin and proteins that can immobilize invading pathogens. However, if NETs accumulate, they can contribute to detrimental autoimmune processes. Thus, we aimed to investigate the impact of NETs in ERU patients. Therefore, we quantified several NET-markers (cell-free DNA, nucleosomes, citrullinated histone H3, histone-myeloperoxidase complexes, interleukin-17, equine cathelicidin 1 and DNase I activity) and NET-autoantibodies in sera and vitreous body fluids (VBF) of ERU-diseased horses and correlated the data with the disease status (signalment, ERU scores and Leptospira infection status). NET markers were detected to varying degrees in VBF of diseased horses, and partially correlated to disease severity and the presence of Leptospira spp.. Free DNA and nucleosomes as NET markers correlate with ERU severity in total and VBF scores, despite the presence of active DNases. Additionally, a significant correlation between fundus affection in the eye and NET autoantibodies was detectable. Therefore, we further examined the influence of patient VBF samples and isolated NETs towards the blood-retina barrier in a cell culture model. VBF of diseased horses significantly induced cytotoxicity in these retinal pigment epithelium cells. Moreover, partially digested NETs equally resulted in cytotoxic effects. In the presence of lipopolysaccharide (LPS) as main component of the leptospiral surface, also undigested as well as completely digested NETs were cytotoxic. Furthermore, correlations of the ERU-scores with Leptospira were calculated. Retrievability of leptospiral DNA, and antibody titers of the serovar Grippotyphosa, correlated with disease severity. Also, a correlation between Leptospira and several NET markers was perceived in VBF. Altogether, our findings suggest a positive correlation between NET markers with disease severity and leptospiral involvement in VBF of ERU-diseased horses, as well as a cytotoxic effect of NETs in eyes.